Rational Drug use in Pakistan: A systematic review - Arshad, Shumaila; Mahmood, Sahar; Rasool, Sidra; Hayat, Saima; Zafar, Shanawar; Zehra, Tehreem (Journal of Pharmacy Practice and Community Medicine)
Background: This article provides a review of different studies about rational use of drugs in Pakistan and different interventions to improve drug use in the country. The analysis of these studies focused on the quality of services offered by these pharmacies, knowledge of drug sellers and dispensing practices. Material and methods: The summary of rational drug use and their possible health consequences is based on reviews of drug use in Pakistan. A systematic inventory of published research work since 1990 to 2015 was undertaken to identify studies which focused on different aspects of rational drug use. Annals and computerized databases of International Network for Rational Use of Drugs (INRUD), WHO, PubMed, Science Direct were screened for relevant journal articles, research reports and newsletters. To expand and fortify the search process, the general search engine Google was utilize. Results: Initially, a total of 60 articles were retrieved for electronic databases by the authors. These articles were then again matched with the objectives of this study and those articles which did not qualify, were excluded. After further screening, 20 articles were selected and 15 appropriate studies were finally included in the review. Conclusion: In this study, we find out that large number of drugs is being used in wrong way. The current paper highlighted that quality of services provided at community pharmacies in Pakistan is not satisfactory. The situation of rational drug use indicators in the hospitals where the study was conducted is alarming. There is an urgent need for intervention to improve the situation.
Keywords: Rational drug use; Irrational drug use; Pakistan